Early Fraud Detection Using the Fraud Triangle Model in Islamic Banking - Hendra, Joni; Marisna, Diska Sendi; Karimah, Uswatun; Sofiyanto, Sofiyanto; Saprudin, M (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the potential for fraud in Islamic banking through the application of the Fraud Triangle Model, which consists of three key elements: pressure, opportunity, and rationalization. Although Islamic banking is founded on Islamic principles such as justice, transparency, and moral responsibility, fraudulent practices may still occur due to human factors and weaknesses in internal control systems. This research employs a literature review method by examining academic sources and relevant regulations. The findings reveal that economic pressure, weak internal oversight, and justifications for unethical behavior are primary drivers of fraud in Islamic financial institutions. Therefore, effective fraud mitigation strategies are needed, including strengthened corporate governance, supervision based on Islamic values, and the development of a work culture grounded in integrity. The application of the Fraud Triangle Model in the Islamic banking context is expected to support early fraud detection and prevention in a more ethical and effective manner.